Effectiveness of Management Accounting Systems, Management Control Systems, and Environmental Uncertainty on Managerial Performance with Decentralization as A Moderation Variable - Difla (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya (UPR), 2024)
This research aims to determine